The abuse of power and sexual violence: a close reading of 2 Samuel 11 against the background of Boko Haram Atrocities in Nigeria - Audu Makama, Bulus (Stellenbosch : Stellenbosch University, 2016)
Thesis (MTh)--Stellenbosch University, 2016.